Pengaruh 4SS (Swaddling, Side, Shushing, Swinging) terhadap Heart Rate Neonatus Paska pengambilan Darah Vena di Ruang Edelweis RSUD Ngudi Waluyo Wlingi - Husna Rahmawati; Erni Setiyorini (Journal of Ners and Midwifery, 2017)
Neonates experience changes in all the systems one of the most dramatic changes is the cardiovascular system. Neonates born in hospitals Wlingi all venous blood should be taken where the effect of this action is definitely cause discomfort which can affect the heart rate of neonates. Techniques that can improve the comfort of one of them with techniques 4Ss (swaddling, side, shush- ing, swinging) The purpose of this study was to determine the effect on heart rate 4Ss post neonatal venous blood sampling.This research design using posttest only control group. The research was conducted at room Edelweiss Ngudi Waluyo Hospital Wlingi for 1 month (5-29 November 2014). Subjects were neonates who meet the inclusion criteria. The total sample of 34 neonates in the two groups of 17 treatment group and 17 control group. Sampling using accidental sampling technique. The collection of data through observation in the treatment group and the control group. Data were analyzed by T-test.The results showed heart rate is lower in the treatment group compare the con- trol group. The results of the statistical test showed P-valiu = 0.001 which means that there is an influence on heart rate 4Ss post neonatal venous blood sampling.It is hoped with this study 4Ss technique can be applied by health workers and parents to provide comfort in neonates.